The Counsellor and Changing Canadian Sexual Mores - Shymko, Delores L. (Canadian Journal of Counselling and Psychotherapy, 2012)
To date, the counsellor in North America has been inadequately trained, and consequently ineffective in dealing with client problems involving human sexuality. The purpose of this paper is to help the counsellor increase his awareness and understanding of the sexual attitudes and behaviour of the clients with whom he interacts in the therapeutic setting. This task is undertaken by examining the empirical findings from some current Canadian sex research to determine some of the dominant changes in attitudes that have occurred within the past decade. The findings from this research have indicated that therehas been a major change in the personal outlook of Canadian youth, as well as the viewpoint of the public at large, leading to a more general acceptance of a permissive sexual ethic. There are also signs that public attitudes toward prevalent social codes of sexual behaviour are being reappraised and redefined. The implications of these changes in Canadian sexual mores as a significant factor in the counselling process are discussed.